Oscillometry changes reflect clinically meaningful improvement after bronchial thermoplasty for uncontrolled asthma: A case report - Niranjan Setty; Alice Crawford; Brooke Kyle; Dhaval Thakkar; Rajesh Thomas; John Blakey (Respirology Case Reports)
Abstract Asthma is a highly prevalent but heterogenous condition. Uncontrolled disease is relatively common and may be due to ongoing inflammation and/or persisting bronchial hyper‐reactivity. Bronchial thermoplasty has been in use for many years but optimal case selection and post‐procedure assessment remain uncertain. We present a case of a gentleman in his 50s with lifelong asthma who experienced a persistent loss of control following influenza A in 2017. Despite multidisciplinary assessment and guideline‐based escalation of therapy, he had persisting symptoms. In the context of his atopy, he was trialled unsuccessfully on dupilumab. Bronchial thermoplasty (BT) was undertaken with good clinical benefit. Although his spirometry was little changed by BT, there was improvement in forced oscillometry technique (FOT) measurements. FOT may therefore be a useful addition to the assessment and monitoring of individuals considered for, or undergoing, BT.